BREAKFAST AND CLASSROOM BEHAVIOUR: AN OBSERVATIONAL STUDY OF GRADE 3 STUDENTS IN A BILINGUAL DEMONSTRATION SCHOOL, IN THAILAND - Webb, Jonathan Richard (PEOPLE: International Journal of Social Sciences, 2017)
This study investigated what students consumed for breakfast and their behaviours within the classroom. It attempted to determine whether there is a relationship with inappropriate, off-task or non-compliant behaviour of students and what they had consumed that morning. Recent literature suggests there is. This was observed using a time sampling, coding system. Breakfast Consumption was recorded by a self-completion questionnaire, using the Australian guide to healthy eating (AGHE) as a dietary guide. Correlational analysis was used to determine the relationship between breakfasts and behaviour, and ANOVA (analysis of variance) was used to determine if any significant relationships existed between each behaviour type and diet. The subjects were 23 Grade 3 students (19 boys, 4 girls) of a university affiliated bilingual school in Thailand. The coding of behaviour was done by trained professional observers using Revised Edition of School Observational Coding System (REDSOCS). The modified dietary recall questionnaire was administered at school over a period of 2 weeks. Upon reanalysis of the data there appeared to be a link between an unhealthy diet and off-task and non-compliant behaviours. However these data were not statistically significant. This study suggests that what is consumed in the morning may not have an important affect on students’ classroom behaviour. It is also possible that culture and socio economic factors may have obscured any effects. It is recommended that further research be done to see if these present findings would hold for more varied populations and other types of Thai schools.